Clinical Characteristics, Laboratory Findings, and Prognosis in Patients With Talaromyces marneffei Infection Across Various Immune Statuses - Li, Dianwu; Liang, Huaying; Zhu, Yiqun; Chang, Qinyu; Pan, Pinhua; Zhang, Yan (Frontiers in Medicine, 2022)
Abstract Purpose Talaromyces marneffei (TM) is an opportunistic fungus that is predominantly prevalent among HIV-positive patients in South-East Asia. However, few studies focused on the clinical features, laboratory findings and prognosis across varying immune states. Methods A total of 54 TM-infected patients in Xiangya Hospital of Central South University from January 1st, 2006 to October 31th, 2021 were retrospectively analyzed. Clinical profiles were compared across the different immune statuses by HIV-positive (HIV group, n=18), HIV negative but with immunocompromised conditions (Non-HIV with IC Group, n=11), and immunocompetent patients (n=25). Results All the patients were diagnosed by pathogen culture or metagenomic next-generation sequencing (mNGS). The median age was 50.0, and patients with HIV were much younger compared to the other two groups. The most common symptom was fever (79.6%), followed by cough (70.4%), weight loss (61.1%), expectoration (53.7%). The HIV-positive patients were more likely to develop into subtype of disseminated TM affecting multiple organs including lymph node, liver, skin and spleen, thus resulting in higher hospital mortality compared to the other two groups. Patients without HIV but with immunocompromised conditions presented similar hospital mortality rate compared to immunocompetent patients, while experienced longer days of hospitalization to recover from the diseases. Additionally, patients with HIV were easily to be diagnosed by pathogen culture in this study, however, mNGS presented as a promising tool to confirm TM in those suspicious patients without HIV. Conclusions In summary, patients with HIV were more likely to develop into disseminated TM and result in higher mortality compared to those patients without HIV. Additionally, mNGS presented as an important supplementary tool to confirm TM infection in HIV-negative patients, particularly in those with immunocompromised diseases.